Study on the Development of Entrepreneurship Education Models Based on MSME Student Program on Students of FE UNJ - Henry ERYANTO; Marsofiyati; Darma Rika SWARAMARINDA; Mayang Puspita DEVI; Novinda ELISIA (Communications of International Proceedings, 2021)
The increasing number of unemployed is a serious development problem. In general, the increasing number of unemployed is caused by the number of available job opportunities that are not balanced with the number of the workforce which increases every year. The problem of unemployment is a problem that has not been completely resolved by the Indonesian government. What's more, for 2020, the virus spreads, which makes the number of unemployed increase drastically. The difficulty of finding a new job in 2020 and the number of companies going out of business, caused employees to be laid off by the company which led to an increase in the number of unemployed. The problem of increasing unemployment is also caused by graduates who prefer to be employees of large companies, so that graduates will only wait for other opportunities if they are not accepted to work in the company.
Keywords: Study; Education Entrepreneurship; Entrepreneurship.